The Educational and Early Occupational Attainment Process - Sewell, William H.; Haller, Archibald O.; Portes, Alejandro (American Sociological Review, 1969)
Blau and Duncan (1967:165–172) have recently presented a path model of the occupational attainment process of the American adult male population. This basic model begins with two variables describing the early stratification position of each person; these are his father’s educational and occupational attainment statuses. It then moves to two behavioral variables; these are the educational level the individual has completed and the prestige level of his first job. The dependent variable is the person’s occupational prestige position in 1962. That the model is not without power is attested by the fact that it accounts for about 26 percent of the variance in educational attainment, 33 percent of the variance in first job, and 42 percent of the variance in 1962 level of occupational attainment. Various additions to the basic model are presented in the volume, but none is clearly shown to make much of an improvement in it. These include nativity, migration, farm origin, subgroup position, marriage, and assortative mating. Without detracting from the excellence of the Blau and Duncan analysis, we may make several observations. Because the dependent behaviors are occupational prestige attainments—attainment levels in a stratification system—it is appropriate to single out variables indicating father’s stratification position as the most relevant social structural inputs. It is unfortunate that practical considerations prevented the inclusion of psychological inputs in their model, especially considering the repeated references to one such—mental ability—in the literature on differential occupational attainment (Lipset and Bendix, 1959:203–226; Sewell and Armer, 1966). More recently, this gap has been partially filled (Duncan, 1968). Also omitted are social psychological factors which mediate the influence of the input variables on attainment. This, too, is unfortunate in view not only of the speculative theory but also the concrete research in social psychology, which suggests the importance of such intervening variables as reference groups (Merton, 1957:281–386), significant others (Gerth and Mills, 1953:84–91), self-concept (Super, 1957:80–100), behavior expectations (Gross et al., 1958), levels of educational and occupational aspiration (Haller and Miller, 1963; Kuvlesky and Ohlendorf, 1967; Ohlendorf et al., 1967), and experiences of success or failure in school (Parsons, 1959; Brookover et al., 1965).